IN SILICO DESIGN OF BENOXAZOLE BEARING AZETIDINONE DERIVATIVES AS VEGFR-2 AGONIST IN CANCER - PN, LEYANA; PT, MANJU; VIJAYAN, MEENU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Cancer is a group of disease characterized by uncontrolled growth of cells. The objective of the study includes the in silico designing of benzoxazole bearing azetidinone derivatives as Vascular Endothelial Growth Factor 2 in cancer. Methods: In silico design of proposed derivatives was conducted using tools such as AutoDock Vina, ACD Lab ChemSketch ver. 12.0, Prediction of Activity Spectra for Substances online, molinspiration, and Swiss ADME. The derivatives obeying Lipinski’s Rule of Five in accordance with molinspiration were selected for docking studies. Results: The data obtained from molinspiration revealed that the designed derivatives have physical and chemical properties meant for an orally bioavailable drug. From the docking studies derivatives BT1 and BT5 showed high docking score which indicate that these derivatives possess high affinity and high polar interaction towards protein 4DBN. Conclusion: The designed benzoxazole bearing azetidinone derivatives were found to possess good binding affinity and good interaction in the binding pocket of the target 4DBN. Therefore, these derivatives are expected to exhibit good anticancer property with minimal side effects.